Mermaid's lament [videorecording (DVD)] - Escobar, Dayva Summer; Mattos, Justina; Gregory, Michael (Actor); Costello, Owen (Indie Rights, 2024)
Dr. Nell Jamison, a brilliant yet haunted psychiatrist, finds her carefully constructed world shattered when she crosses paths with Oee, a young woman who insists she is a mermaid. Oee's unyielding assertion of her mermaid identity forces Nell to reevaluate the fragile balance between perception and reality and plunge into her own psyche. Their bond becomes a conduit for exploring the depths of the human experience, where self-discovery, empathy, and the profound mysteries of the sea intertwine.